Fetomaternal Outcome in Hypertensive Disorder of Pregnancy in a Tertiary Care in India: A Prospective Observational Study - Raj, Sweety; Bansal, Disha; Dalmia , Kanchan; Jaiswal, Priya (Research Developments in Medicine and Medical Science Vol. 1, 2023)
The purpose of the study is to evaluate the foetal and maternal outcomes in tertiary care pregnancy affected by hypertensive disorders. The study aims to investigate both maternal and foetal morbidity, including low Apgar scores, meconium aspiration syndrome, NICU admissions, and fatalities. Maternal morbidity includes complications, hospital stays, and mortality. Pre-eclampsia continues to be the main cause of pregnancy-related hypertension, which affects 12–22% of pregnancies and complicates 10% of them. It is defined as the sudden onset of proteinuria and elevated blood pressure (BP) in a previously normotensive woman after 20 weeks of pregnancy (BP 140/90 and 0.3 g protein in 24 h urine specimen). . This was a prospective observational study conducted in the department of obstetrics and gynecology at Rohilkhand medical college and hospital, Bareilly between 1st November 2018 and 31st October 2019. Hypertension associated with pregnancy, whether it is pre- existent or developed during pregnancy, is one of the most common condition encountered by obstetricians. From 100 patients, pre-eclampsia and pre-eclampsia superimposed on chronic HTN was among 53% and 3% patients. Eclampsia and gestational HTN was in 37% and 7% of patients. Birth weight >2.5 kg was among 52% and 2.01–2.5 kg was in 36% patients. In our study, 12.7% of neonates needed NICU admission at birth. Majority of patients had unbooked deliveries. About half of the patients in the study were of term pregnancy. Majority of patients had emergency LSCS (72%) followed by spontaneous vaginal delivery (28%). Deranged LFT was the most common abnormal maternal investigation (38%). Stillbirths was in 29% in which 21% old IUD and 8 % stillbirth. There were 71% live births.